ФІЛОСОФІЯ БІЗНЕСУ: ПРЕДМЕТНЕ ПОЛЕ І ОСНОВНІ ПАРАДИГМИ. - Ю. В., Ковбасюк (Hileya: Scientific Bulletin / Gileya, 2025)
The purpose of the study is to conceptualize the modern understanding of the phenomenon of business philosophy, its subject field and current paradigms. In accordance with the specified goal, the following tasks are implemented in the work, such as: 1) modern approaches to understanding and interpretation of the content of the phenomenon of business philosophy are summarized; 2) the content and nature of the subject field of modern business philosophy is determined; 3) the content of paradigms inherent in modern business philosophy is outlined. The work shows that the subject field of modern business philosophy is expressed by the relationship “Business – Society”, since business philosophy includes its analysis of the phenomenon of business itself, the regularities of its development and functioning in the social space, as well as the specifics of the relationship between business and society. It is emphasized that the humanistic pathos of business philosophy is in the fact that in a practical context, business philosophy (as a concept and worldview model) is oriented towards people and their interests. The position is defended that the philosophical understanding of business, as well as the relationship “Business – Society” provides an opportunity for business to remain within the limits of the socially approved humanistic paradigm. According to the results of the research, the authors can identify the paradigms that are relevant for business philosophy, such as the circular economy paradigm, the paradigm of social responsibility, as well as the Ukrainian paradigm of business philosophy, which is based on the idea of the importance of spiritual and practical values. The outlined paradigms form the methodological basis of social and philosophical analysis of modern business, and act as practical guidelines in the context of creating current strategies for the development of national business.